Effect of Nitrogen Doping on Variability of TaOx -RRAM for Low-Power 3-Bit MLC Applications. (22nd January 2015) - Misha, Saiful Haque; Tamanna, Nusrat; Woo, Jiyong; Lee, Sangheon; Song, Jeonghwan; Park, Jaesung; Lim, Seokjae; Park, Jaehyuk; Hwang, Hyunsang
Abstract : The switching uniformity and reliability of the TaOx based resistive random access memory (RRAM) device were investigated with varying nitrogen doping concentration. The nitrogen doped samples shows excellent electrical and reliability characteristics such as small switching variability for 3-bit multilevel per cell (MLC), low power operation and good retention properties. Compared with control sample, improved device characteristics of nitrogen doped device can be explained by nitrogen induced filament confinement.